Mudarabah di BSI Cabang Kota Ternate (Bank Sebagai Mudharib, Metode Bagi Hasil & Bank Sebagai Agent Investasi - Abd Wahab, Abdul Muis; Malaka, Mulis (Peneliti.net, 2026)
Diversity in Indonesian society is seen as both a destiny and a gift from Allah SWT that must be preserved and nurtured. Therefore, diversity is not seen as a source of problems, but rather as a strategic potential that can strengthen national unity if managed well. However, the diversity of ethnicities, languages, and religions also has the potential to cause conflict if not handled wisely. This research aims to analyze the values of religious moderation at State Senior High School 5 South Halmahera and to determine the form of Islamic Religious Education (PAI) learning in implementing religious moderation at the school. This research uses a qualitative method with a descriptive approach, which attempts to deeply uncover various social phenomena related to the implementation of religious moderation in school life. The research results indicate that the implementation of religious moderation values at SMA Negeri 5 Halmahera Selatan is carried out thru the learning process in the classroom. The values developed include helpfulness, acceptance of differences, mutual respect, compassion, tolerance (tasamuh), balance (tawazun), justice (ta'adl), moderation (tawasuth), and mutual cooperation. These values are taught not only in Islamic Religious Education (PAI) lessons but also thru interfaith understanding, such as the teachings of love in Christian theology, and in Islamic Cultural History (SKI) materials, which emphasize an inclusive and moderate attitude in religious life.